FEATURES OF FORMATION OF THE COST PRICE OF PASSENGER TRANSPORTATION BY THE AUTOMOBILE TRANSPORT - A. Aredova; I. Shchegoleva (Вестник университета)
The article is devoted to the issues of determining the magnitude of the dependence of ratio of indirect costs and other expenses on ordinary activities to variable expenses in order to calculate the cost of 1 km of the public vehicle. The necessary correction, based on the results of the approbation, of the obtained results, which will allow to take into account the planned expenditures of the local budget for the organization of passenger transportation by public transport, was carried out. The article is given general characteristic of the cost price of transportation of passengers by public transport.